Lateral spreading and associated slope processes in fractured rock slabs - Spreafico, Margherita Cecilia <1984> (Alma Mater Studiorum - Università di Bologna, 2015)

(untitled)
Landslides of the lateral spreading type, involving brittle geological units overlying ductile terrains, are a common occurrence in the sandstone and limestone plateaux of the northern Apennines of Italy. These instability phenomena can become particularly risky, when historical towns and cultural heritage sites built on the top of them are endangered. Neverthless, the mechanisms controlling the developing of related instabilities, i.e. toppling and rock falls, at the edges of rock plateaux are not fully understood yet. In addition, the groundwater flow path developing at the contact between the more permeable units, i.e. the jointed rock slab, and the relatively impermeable clay-rich units have not been already studied in details, even if they may play a role in this kind of instability processes, acting as eventual predisposing and/or triggering factors. Field survey, Terrestrial Laser Scanner and Close Range Photogrammetry techniques, laboratory tests on the involved materials, hydrogeological monitoring and modelling, displacements evaluation and stability analysis through continuum and discontinuum numerical codes have been performed on the San Leo case study, with the aim to bring further insights for the understanding and the assessment of the slope processes taking place in this geological context. The current research permitted to relate the aquifer behaviour of the rocky slab to slope instability processes. The aquifer hosted in the fractured slab leads to the development of perennial and ephemeral springs at the contact between the two units. The related piping erosion phenomena, together with slope processes in the clay-shales led to the progressive undermining of the slab. The cliff becomes progressively unstable due to undermining and undergoes large-scale landslides due to fall or topple.